Synthesis of 2,3-dihydrobenzofurans via a photochemical gold-mediated atom transfer radical addition reaction - Melder, Julian J.; Witzel, Sina; Terres, Sophia; Bary, Philippe de; Krohne, Lukas; Rudolph, Matthias; Hashmi, A. Stephen K. (Organic letters, 2024)
A light-mediated cyclization reaction initiated by an atom transfer radical addition (ATRA) of haloalkanes onto alkenes was exploited for the synthesis of functionalized dihydrobenzofurans. Initial investigation indicated that the dimeric gold catalyst [Au2(μ-dppm)2Cl2] can effectively be used for intermolecular ATRA reactions. Further, the reactivity was applied in a cascade-like cyclization for the preparation of dihydrobenzofuran derivatives. With the presented photochemical approach, the functionalization can be achieved directly from ortho-allylphenols in yields of up to 96% under mild conditions.